Research progress of ophthalmic preparations of immunosuppressants - Ye Liu; Haonan Xu; Na Yan; Zhan Tang; Qiao Wang (Taylor & Francis Group, 2023)
AbstractImmune ophthalmopathy is a collection of autoimmune eye diseases. Immunosuppressants are drugs that can inhibit the body's immune response. Considering drug side effects such as hepatorenal toxicity and the unique structure of the eye, incorporating immunosuppressants into ophthalmic nanodrug delivery systems, such as microparticles, nanoparticles, liposomes, micelles, implants, and in situ gels, has the advantages of improving solubility, increasing bioavailability, high eye-target specificity, and reducing side effects. This study reviews recent research and applications of this aspect to provide a reference for the development of an ophthalmic drug delivery system.